A 19‐Mb de novo deletion on BTA 22 including MITF leads to microphthalmia and the absence of pigmentation in a Holstein calf. (9th September 2014) - Wiedemar, Natalie; Drögemüller, Cord
Summary Mutations in MITF lead to a large variety of phenotypes in human, mice and other species. They mostly affect pigmentation and hearing, whereas in mice, they may additionally cause microphthalmia and osteopetrosis. In this study, we report a single case of a Holstein calf with lack of pigmentation and microphthalmia born to healthy parents. Mendelian analysis of high‐density SNP genotypes reveals a large number of parentage errors showing missing paternal alleles in the offspring, indicating a deletion encompassing 19 Mb on BTA 22. The genomic deletion affects the paternal allele and includes MITF and 131 other annotated genes. As the calf shows only one copy of the BTA 22 segment, the observed phenotype is probably caused by haploinsufficiency of the genes in that genomic region. Both the observed lack of skin pigmentation and reduced eye size can most likely be explained by a lack of MITF function.